2021
DOI: 10.1002/pbc.28908
|View full text |Cite
|
Sign up to set email alerts
|

ONCOPEDS: A mobile application to improve early diagnosis and timely referral in childhood cancer in a low‐ and middle‐income country—A pilot study

Abstract: Background Diagnosis delay in children and adolescents with cancer is a public health problem in Peru that leads to high rates of advanced disease and mortality. We aimed to assess the implementation feasibility and potential utility of ONCOpeds®, a mobile application that provides consultations with pediatric oncologists, in reducing the latency to diagnosis (LD) and referral time (RT) among children and adolescents in Peru diagnosed with cancer. Material and Methods A prospective pilot study was conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…87 The remote management of oncological patients was first assessed on 2018 in a pilot study with the mobile app ONCOpeds, which reported that use of the app improved diagnosis and referral time in pediatric cancer patients. 88 However, this app remained as a pilot and was never launch to the general public. Another important application of telemedicine in Peru has been the monitoring of tuberculosis cases.…”
Section: Introductionmentioning
confidence: 99%
“…87 The remote management of oncological patients was first assessed on 2018 in a pilot study with the mobile app ONCOpeds, which reported that use of the app improved diagnosis and referral time in pediatric cancer patients. 88 However, this app remained as a pilot and was never launch to the general public. Another important application of telemedicine in Peru has been the monitoring of tuberculosis cases.…”
Section: Introductionmentioning
confidence: 99%
“…Reputation incentives contribute in the same way, particularly when information on the performance of professionals is published [ 6 ]. In turn, the incorporation of technologies has proven to be useful to facilitate learning, cooperation, better promotion and monitoring procedures, especially in rural setups, constituting a complement to care at the first level [ 52 , 70 , 75 , 88 , 93 , 99 , 141 , 143 ].…”
Section: Priority Areas For the Development Of Phc Strategies And Hea...mentioning
confidence: 99%
“…In Peru there is a mobile application, called ONCOPEDS, that aims to facilitate early diagnosis and education not only to health care providers, but parents and teachers. ONCOPEDS has promising results so far improving the referral time and education in Peru ( 44 ).…”
Section: Regional and International Interventionsmentioning
confidence: 99%